2016
DOI: 10.48550/arxiv.1602.03155
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

From K.A.M. Tori to Isospectral Invariants and Spectral Rigidity of Billiard Tables

Abstract: This article is a part of a project investigating the relationship between the dynamics of completely integrable or "close" to completely integrable billiard tables, the integral geometry on them, and the spectrum of the corresponding Laplace-Beltrami operators. It is concerned with new isospectral invariants and with the spectral rigidity problem for the Laplace-Beltrami operators ∆ t , t ∈ [0, 1], with Dirichlet, Neumann or Robin boundary conditions, associated with C 1 families of billiard tables (X, g t ).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 61 publications
(181 reference statements)
0
7
0
Order By: Relevance
“…In fact, there do not even exist prior 'local spectral determination' results, which would say that an ellipse (or any other domain) is determined by its spectrum among domains which lie in a sufficiently small C k neighborhood of the ellipse. The only prior positive result specific to the inverse Laplace spectral problem for ellipses is [HeZe12] (see also [PoTo16] for ellipsoids), which says that ellipses are infinitesimally spectrally rigid among C ∞ domains with the same left-right and up-down symmetries. The progress in that article is to allow competing domains to be C ∞ and not real-analytic.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, there do not even exist prior 'local spectral determination' results, which would say that an ellipse (or any other domain) is determined by its spectrum among domains which lie in a sufficiently small C k neighborhood of the ellipse. The only prior positive result specific to the inverse Laplace spectral problem for ellipses is [HeZe12] (see also [PoTo16] for ellipsoids), which says that ellipses are infinitesimally spectrally rigid among C ∞ domains with the same left-right and up-down symmetries. The progress in that article is to allow competing domains to be C ∞ and not real-analytic.…”
mentioning
confidence: 99%
“…The results of the present article, by comparison, do not make any symmetry assumptions and allow the competing domains to be general C ∞ domains. There also exists a sequence of results of PoTo12,PoTo16] using the KAM structure of convex smooth plane domains to deduce spectral rigidity results for Liouville billiards (including ellipses) with two commuting reflection symmetries, and for analytic domains that are sufficiently close to an ellipse and possess the two reflection symmetries of the ellipse.…”
mentioning
confidence: 99%
“…There is also a series of articles of G. Popov and P. Topalov (see e.g. [PoTo03,PT16]) on the use of KAM quasi-modes to study Laplace inverse spectral problems. In particular, in [PT16], Popov-Topalov also give a new proof of the rigidity result of [HeZe12] and extend it to other settings.…”
Section: Related Results and Open Problemsmentioning
confidence: 99%
“…[PoTo03,PT16]) on the use of KAM quasi-modes to study Laplace inverse spectral problems. In particular, in [PT16], Popov-Topalov also give a new proof of the rigidity result of [HeZe12] and extend it to other settings. The approach in this article is closely related to theirs, although it does not seem that the authors directly studied Cauchy data of eigenfunctions of an ellipse.…”
Section: Related Results and Open Problemsmentioning
confidence: 99%
“…In [HZ10], it was shown that real analytic domains in R n with reflectional symmetries about all coordinate axes are spectrally determined among the same domains. In [HZ10], ellipses were shown to be to infinitesimally spectrally rigid among smooth domains with the symmetries of the ellipse (see [PT03,PT12,PT16] for results in the context of completely integrable tables other than ellipses). Guillemin-Melrose [GM79a] showed Robin spectral rigidity of ellipses when the Robin functions preserve both reflectional symmetries.…”
Section: Introductionmentioning
confidence: 99%